Understanding agroecological domains: The key to a successful participatory plant breeding program - Rana, Ram B.; Sthapit, B.R.; Subedi, A.; Rijal, D.K.; Chaudhary, P. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Farmers have an intricate knowledge of their agro ecological domains. The empirical evidences from Kachorwa (terai) and Begans (mid-hill) sites in Nepal suggest that farmers distinguish domains for rice primarily on the basis of moisture and fertility. Farmers also differentiate the number, relative size, and specific characteristics of each domain within a given geographic area. Similarly, they allocate Individual varieties landraces to each domain, indicating that the competition between varieties landraces occurs within the domain and that transgression of domain was rather limited. These deductions need to be verified at a wider level. A fuller understanding by researchers of specific agro ecological domains is a prerequisite for them to contribute substantially in planning and executing effective participatory plant breeding (PPB) programs. Only with a sound knowledge of agro ecological domains and the varietal distribution within domains can a program on diversity deployment and biodiversity conservation be effectively implemented. Likewise, justifying Ihe cost-effectiveness of PPB, targeting research extension activities, and measuring the contribution of PPB to food security demands a detailed understanding of agro ecological domains. Simple and practical ways to illicit information on agro ecological domains and associated varieties landraces through farmer' group discussion al the village level have been suggested as a pre-project activity for PPB, which could enhance the success of PPB programs.